2021
DOI: 10.1186/s12884-021-04101-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio for the prediction of histological chorioamnionitis in cases of preterm premature rupture of membranes: a case-control study

Abstract: Background The neutrophil-lymphocyte ratio (NLR) is easily calculated blood test parameter, which can be used as marker to predict many inflammatory disorders. The aim of this study was to assess and compare the NLR in maternal blood with the white blood cell (WBC) count and C-reactive protein (CRP) concentration for the prediction of histological chorioamnionitis. Methods This was a case-control study of 137 woman with preterm premature rupture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…In the context of PPROM, several studies have suggested that patients with acute HCA have increased WBC counts, NLR, and CRP levels compared with those without HCA 58–61 . In line with these findings, 58–61 our results revealed independent associations of elevated levels of CRP, WBC counts, and NLR in maternal blood with acute HCA. The main advantages of these widely used laboratory tests are that they can provide a fast, simple, easy, and inexpensive way of assessing acute HCA; however, they are not sufficiently specific or sensitive when applied alone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the context of PPROM, several studies have suggested that patients with acute HCA have increased WBC counts, NLR, and CRP levels compared with those without HCA 58–61 . In line with these findings, 58–61 our results revealed independent associations of elevated levels of CRP, WBC counts, and NLR in maternal blood with acute HCA. The main advantages of these widely used laboratory tests are that they can provide a fast, simple, easy, and inexpensive way of assessing acute HCA; however, they are not sufficiently specific or sensitive when applied alone.…”
Section: Discussionsupporting
confidence: 89%
“…In the context of PPROM, several studies have suggested that patients with acute HCA have increased WBC counts, NLR, and CRP levels compared with those without HCA 58–61 . In line with these findings, 58–61 our results revealed independent associations of elevated levels of CRP, WBC counts, and NLR in maternal blood with acute HCA.…”
Section: Discussionsupporting
confidence: 89%
“…38 Although lymphocytes may also be predictors of HCA, we found NLR to be of higher value. By evaluating the predictive value of NLR in patients with PPROM and HCA, a recent study by Balciuniene et al 39 found that NLR also had a good predictive value, which was not significantly different from that of CRP.…”
Section: Discussionmentioning
confidence: 99%
“…CRP levels and NLR, as indicators of systemic inflammation, have many advantages in the clinical setting, such as low cost, fast performance, and simplicity when assessing acute HCA; however, they are not sufficiently sensitive or specific to detect inflammation in the body. In the context of PPROM, previous studies showed that increased CRP levels and NLR in maternal blood would be useful to identify patients at risk of acute HCA 69–71 . However, to date, little information is available on whether these two blood markers, which are the most commonly used in the clinic, are also useful for detecting acute HCA in PTL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of PPROM, previous studies showed that increased CRP levels and NLR in maternal blood would be useful to identify patients at risk of acute HCA. [69][70][71] However, to date, little information is available on whether these two blood markers, which are the most commonly used in the clinic, are also useful for detecting acute HCA in PTL patients. Indeed, most studies have been conducted in mixed patient populations, including both PTL and PPROM patients, 72,73 In the present study, which only included patients with PTL, we did not find independent associations of increased blood levels of CRP or NLR with acute or microbial-associated HCA, although these associations were significant in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%